P1130A CELLULAR MODEL OF HUMAN MESOTHELIUM TO STUDY OF WATER TRANSPORT DURING PERITONEAL DIALYSIS AND THE BIOCOMPATIBILITY OF INNOVATIVE GLUCOSE-SPARING SOLUTIONS. (6th June 2020) - Piccapane, Francesca; Caroppo, Rosa; Arduini, Arduino; Corciulo, Roberto; Russo, Roberto; Divino, Jose Carolino; Bonomini, Mario; Gerbino, Andrea; Carmosino, Monica; Svelto, Maria; Procino, Giuseppe
Abstract: Background and Aims: The three pore model postulates that the endothelium of peritoneal capillaries is the major limiting barrier regulating water transport across peritoneal membrane during peritoneal dialysis (PD). We hypothesize that the mesothelium may represent an additional selective barrier to water diffusion in PD. We previously demonstrated that the water channel AQP1 is expressed in vivo by mesothelial cells. Here, we characterized an immortalized cell line of human mesothelium (HMC) to study the functional role of the water channel AQP1 in mediating water transport during PD and also to test the biocompatibility of glucose-sparing PD solutions (Xylocore), containing xylitol and L-carnitine as the main osmotic agents. Method: Cells were grown onto porous cell culture inserts to achieve polarization. Polarization was demonstrated by expression of the tight junction markers Zo-1 and occludin. Transepithelial water transport was measured by TEA + -sensitive microelectrodes. HMC cell monolayers were exposed to PD solutions at the apical side for 8 hours. The biocompatibility of conventional versus innovative PD solutions was evaluated by MTT-test, measurement of transepithelial electrical resistance (TEER) and production of pro-inflammatory cytokines by by Luminex xMAP technology. Results: HMC cells showed polarized expression of Na + /K + -ATPase and tight junctions markers but no endogenous expression of AQP1. HMC showed a low TEER (40Ω/cm 2 ) compared to renal cells not expressing AQP1(1000Ω/cm 2 ). However, the transepithelial water transport was comparable between the two cell types. Experiments in HMCs transfected with AQP1 cDNA, suggested that the water permeability of HMC was increased by two-fold in the presence of AQP1. Biocompatibility assays indicated that in conventional dialysis solutions glucose concentration decreased cell viability in a dose-dependent manner. Glucose concentration also strongly decreased the TEER, suggesting reduction of the barrier integrity, and increased pro-inflammatory cytokines production. Interestingly, substitution of part of the glucose with xylitol and L-carnitine minimized these effects. Conclusion: These results suggest that the mesothelium may represent an additional selective barrier regulating water transport through the water channel AQP1 in PD. Importantly, we also demonstrate that the formulation of glucose-sparing PD solutions containing xylitol and L-carnitine better preserve mesothelial cells viability and may represent a useful means to prolong the dialysis life of patients undergoing peritoneal dialysis.